Analisis Keterampilan Abad 21 Siswa Dalam Pembelajaran Biologi - Ananda Putri; Nirwana Anas; Miza Nina Adlini (LPPM Politeknik Pratama, 2023)
This study aims to determine the percentage level of 21st century skills in students at SMA Negeri 1 Beringin in Biology Learning. The research methodology uses descriptive quantitative descriptive research. The research population was students of class X-1 and X-2 of SMA Negeri 1 Beringin with a total sample of 69 students. Data collection techniques with interviews, test instruments, observation sheets and documentation. Data analysis techniques using validity and reliability tests and analysis using percentage value analysis. The results showed that the 21st century skill level of SMA Negeri 1 Beringin students in Biology Learning obtained a percentage score of 72.28% in the good category. The percentage value of each aspect of 21st century skills is critical thinking skills 75.00%, creative thinking skills 61.08%, communication skills 76.81%, and collaboration skills 75.94%.